2002
DOI: 10.1021/ar000145a
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Lewis Acid Catalysts for Selective Organic Reactions in Aqueous Media

Abstract: New types of Lewis acids as water-compatible catalysts have been developed. Various metal salts were found to work as Lewis acid catalysts in aqueous media, and catalytic asymmetric aldol reactions in such media have been attained. Furthermore, Lewis acid-surfactant combined catalysts, which can be used for reactions in water without using any organic cosolvents, have been also developed. These investigations will contribute to reducing the use of harmful organic solvents and to develop efficient catalytic sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
282
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 744 publications
(288 citation statements)
references
References 37 publications
(48 reference statements)
2
282
0
4
Order By: Relevance
“…(a) Lewis acid strength21 correlates with 4‐methylsyringol ( 9 a ) yields; (b) yields of 4‐methylphenols versus 4‐(1‐propenyl)phenols as a function of Sc(OTf) 3 loading, demonstrating the ability to tune product distribution.…”
mentioning
confidence: 99%
“…(a) Lewis acid strength21 correlates with 4‐methylsyringol ( 9 a ) yields; (b) yields of 4‐methylphenols versus 4‐(1‐propenyl)phenols as a function of Sc(OTf) 3 loading, demonstrating the ability to tune product distribution.…”
mentioning
confidence: 99%
“…35,36 As was the case for DA reactions, rare-earth metal(III) triflates have also been successfully employed to promote heteroDiels-Alder reactions. [10][11][12][13][14][15] Below are notable examples of M(OTf) 3 -catalyzed HDA reactions published in the last five years.…”
Section: Hetero-diels-alder Reactionsmentioning
confidence: 99%
“…73 Owing to their oxophilic character, water tolerability and pronounced Lewis acidic properties, lanthanide triflates were also successfully employed in a number of free radical processes. [10][11][12][13][14][15] Yang and co-workers have disclosed Yb(OTf) 3 -promoted 5-/6-exo-trig radical cyclization of α-phenylseleno amido esters 93 under UV irradiation to give rise to mono-and bicyclic nitogen heterocycles 94 (Scheme 26). 74 It was suggested that Yb(OTf) 3 played a two-fold role in promoting the radical process: increased electrophilicity of the α-radical intermediate via 1,3-dicarbonyl moiety chelation and accelerated PhSe group transfer.…”
Section: Radical Cyclizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nacci and co-workers reported (232) PdÁcarbene ligand catalyzed the carbonylation of aryl halides (114) in ILs (Scheme 36). Among the ILs used, tetrabutylammonium bromide (TBAB) was found to give better results.…”
Section: Carbonylation Of Aryl Halidesmentioning
confidence: 99%